Penerapan Insinerator Ramah Lingkungan Berbasis Sistem Minim Asap Guna Mengoptimalisasi Pengelolaan Sampah di Balikpapan Utara - Hijriah Hijriah; Nurul Azizah; Satrio Andi Wicaksono; Ni Putu Amanda Oktavia; Renalita Ridha Shintya; M. Fariz Bhagaskara; Patianus Gwijangge; Abyan Naufal Abdullah; Dicky Himawan; M. Ariel Eka Setiawan (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
Waste management in Karang Joang, North Balikpapan faces some issues due to high-density rental housing, which drives a rapid increase of domestic waste generation and dependence on open burning practices that produce harmful emissions. This community program, conducted by Social Innovation Group 122 of Institute of Technology Kalimantan, aimed to improve community capacity and environmental awareness through three integrated programs: waste sorting workshop with plastic upcycling training, environmental education for kindergarten children (“Little Green Hero”), and a construction and commissioning of a low-smoke incinerator. The program employed a participatory approach combining both theoretical and hands-on practice. Evaluation was conducted through pretest and posttest assessments alongside an 11-indicator Likert questionnaire distributed to 40 respondents. Results demonstrated a significant increase in community understanding, with average scores rising from 80 to 99, and 92.5% of respondents achieving perfect scores. Program acceptance scores reached a maximum of 4.70 out of 5. The low-smoke incinerator, operating via double combustion at above 600°C, is now fully operational, supported by locally trained operators. This program contributes to the achievement of SDGs Goals 3, 11, and 12.